Determinants of birth asphyxia among newborns in Debre Berhan referral hospital, Debre Berhan, Ethiopia: a case-control study - Sisay Shine Tegegnework; Yeshfanos Tekola Gebre; Sindew Mahmud Ahmed; Abrham Shitaw Tewachew (BMC, 2022)
Abstract Background Birth asphyxia is the major public health problem in the world. It is estimated that around 23% of all newborn deaths are caused by birth asphyxia worldwide. Birth asphyxia is the top three causes of newborn deaths in sub-Saharan Africa and more than one-third of deaths in Ethiopia. Therefore, the aim of this study was to identify determinants of birth asphyxia which can play a crucial role to decrease the death of newborns. Methods Unmatched case-control study design was implemented among 276 (92 cases and 184 controls) newborns from January 1st to March 30th, 2020. A systematic sampling technique was used to select the study participants. Data were collected by using a semi-structured interviewer-administered questionnaire and document review by trained nurses and midwives who work at the delivery ward of the hospitals. Bivariate logistic regression analysis was done to identify determinants of birth asphyxia. Adjusted odds ratios with 95% confidence intervals and p-value less than and equal to 0.05 were used to assess the level of significance. Results In this study, maternal education of being can't read & write [AOR = 4.7, 95% CI: (1.2, 11.9)], ante-partum hemorrhage [AOR = 7.7, 95% CI: (1.5, 18.5)], prolonged labor [AOR =13.5, 95% CI: (2.0, 19.4)], meconium stained amniotic fluid [AOR = 11.3, 95% CI: (2.7, 39.5)], breech fetal presentation [AOR = 4.5, 95% CI: (2.0, 8.4)] and preterm birth [AOR: 4.1, 95% CI: (1.8, 9.2)] were factors which showed significantly associated with birth asphyxia among newborns. Conclusions In this study, maternal education can't read & write, antepartum hemorrhage, prolonged labor, stained amniotic fluid, breech fetal presentation, preterm birth were significantly associated with birth asphyxia. So, educating mothers to enhance health-seeking behaviors and close monitoring of the labor and fetus presentation were recommended to reduce birth asphyxia.